2022
DOI: 10.1136/bmjresp-2021-001137
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and frequency of key outcomes in acute severe asthma in children: a Paediatric Research in Emergency Departments International Collaborative (PREDICT) multicentre cohort study

Abstract: RationaleSevere acute paediatric asthma may require treatment escalation beyond systemic corticosteroids, inhaled bronchodilators and low-flow oxygen. Current large asthma datasets report parenteral therapy only.ObjectivesTo identify the use and type of escalation of treatment in children presenting to hospital with acute severe asthma.MethodsRetrospective cohort study of children with an emergency department diagnosis of asthma or wheeze at 18 Australian and New Zealand hospitals. The main outcomes were use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
10
0
4
Order By: Relevance
“…It is therefore apparent, that existing recommendations for the best management of severe acute paediatric asthma are currently based on suboptimal evidence with inconsistent, inconclusive or absent results and a paucity of adequately powered randomised controlled trials. Large observational studies have identified that some outcomes (such as intubation) are likely too rare to be used as primary outcome measures, and practice-changing studies will require collaboration between a large number of centres 37. There remains an urgent need for a global agreement regarding optimised trial designs with the most relevant core outcome measures to provide better evidence to inform future clinical practice 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore apparent, that existing recommendations for the best management of severe acute paediatric asthma are currently based on suboptimal evidence with inconsistent, inconclusive or absent results and a paucity of adequately powered randomised controlled trials. Large observational studies have identified that some outcomes (such as intubation) are likely too rare to be used as primary outcome measures, and practice-changing studies will require collaboration between a large number of centres 37. There remains an urgent need for a global agreement regarding optimised trial designs with the most relevant core outcome measures to provide better evidence to inform future clinical practice 19…”
Section: Discussionmentioning
confidence: 99%
“…Large observational studies have identified that some outcomes (such as intubation) are likely too rare to be used as primary outcome measures, and practice-changing studies will require collaboration between a large number of centres. [38] There remains an urgent need for a global agreement regarding optimized trial designs with the most relevant core outcome measures to provide better evidence to inform future clinical practice. [19] The overall guideline quality was moderate in our study, with high ratings for clarity of presentation, scope and purpose.…”
Section: Children[27]mentioning
confidence: 99%
“…A recent large study described in-hospital management of acute asthma exacerbations in Australia and New Zealand. In 14 029 children, there was a higher overall rates of escalated therapy (7.3% overall, with 4.2% receiving parenteral bronchodilators and 4.3% respiratory support) 12. A common indication for escalation of care is failure to adequately respond to first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] While many children have mild to moderate exacerbations and are discharged home, a recently published study of 14 029 children presenting to Australasian EDs found that 36% of children with acute asthma are admitted to hospital, with 1.1% requiring paediatric intensive care unit admission (PICU). 5 In addition, recent studies document increasing PICU admission for severe acute asthma worldwide. 4 Despite this concerning scenario, the evidence base informing treatments for these high-risk patients with severe presentations is weak.…”
Section: Introductionmentioning
confidence: 99%